Faktor Pendukung Minat Belajar IPAS Siswa Kelas IV SDN 128 Palero Kecamatan Lilirilau Kabupaten Soppeng - Sudarto, Sudarto; Muh. Idris Jafar; Rahma Nur Alifya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is a descriptive qualitative case study aimed to explore the factors influencing the interest in learning science among fourth-grade students at SDN 128 Palero, Lilirilau District, Soppeng Regency. The subjects or participants in this study were five students, five parents, one fourth-grade homeroom teacher, and one headmasterl. Data collection techniques included observation, semi-structured interviews, open-ended questionnaires, and document analysis. Data analysis followed the Miles and Huberman (1994) model, which includes data reduction, data display, and verification. Data validity was ensured through source triangulation (comparing data from students, parents, teachers, and the principal) and method triangulation (integrating observations, interviews, questionnaires, and documents). Results and conclusions: The interest in learning science among fourth-grade students at SDN 128 Palero is supported by a synergy of mutually reinforcing internal and external factors, creating a meaningful learning ecosystem. Internal student factors: high curiosity about natural phenomena, strong intrinsic motivation, active independent learning (searching for external information), and positive enthusiasm during learning. External factors: teacher role: varied strategies (experiments, discussions, projects), local contextual approaches, effective media (visual, concrete), engaging practicums, and ability-based differentiation; parental support: adequate facilities, daily mentoring, motivation (praise, rewards), and collaborative activities such as gardening; school environment: conducive physical conditions, peer social support, complete facilities (labs, digital media), and proactive leadership (RKS, BOS funds, supervision, OSN) and community environment: the relevance of Palero's agrarian practices to household practices (gardening, nature observation).